A widely used spectrophotometric assay to quantify olive oil biophenols according to the health claim (EU Reg. 432/2012). Issue 10 (5th February 2016) - Reboredo‐Rodríguez, Patricia; Valli, Enrico; Bendini, Alessandra; Di Lecce, Giuseppe; Simal‐Gándara, Jesus; Gallina Toschi, Tullia
Abstract : The purpose of this work was to find a simple, cheap, and suitable method, among the most widely employed, able to guarantee a proper determination and quantification of the phenolic content of extra virgin olive oils (EVOOs), in order to satisfy the requirements of the specific health claim (EU Reg. 432/2012). Total phenolic content by Folin–Ciocalteu (FC) was used and compared versus phenolic profile by HPLC‐UV, considering this latter as the most sensitive and specific method for evaluating the phenolic content. Both protocols were performed before and after an acid hydrolysis of the polar phenolic fraction that involves a break of the bound forms of hydroxytyrosol (HTyr) and tyrosol (Tyr), with a simplification of the phenolic profile, and quantification of their total free forms. Results of the phenolic compounds of twelve EVOOs, determined by the different analytical approaches, were statistically compared by means of two‐tailed paired t ‐tests: data obtained by the FC assay (expressed as HTyr) before and/or after acid hydrolysis were statistically comparable with results obtained by acid hydrolysis‐HPLC (as sum of HTyr and Tyr). Practical applications: The promising results obtained in this study show that the simple and cheap colorimetric assay based on the use of the FC reagent, commonly used for the evaluation of phenolic compounds in hydro‐alcoholic extracts of EVOO, can be also efficiently applied, without acid hydrolysis of extracts and HPLC analysis, to verify the compliance to the polyphenols health claim introduced by EU Reg. 432/2012. In fact, in order to preserve the positive image of EVOO due to its healthy properties, it is necessary i) to share an analytical protocol to determine the amount of hydroxytyrosol and its derivatives having a demonstrated effect of protection of blood lipids from oxidative stress ii) to check by this protocol if EVOOs satisfy the EU requirement for including the specific health claim on the oil label. The simple and cheap Folin–Ciocalteu colorimetric assay, commonly used for the evaluation of phenolic compounds in hydro‐alcoholic extracts of EVOO, can also be efficiently applied to verify the compliance to the health claim introduced by EU Reg. 432/2012. Abstract : The simple and cheap Folin–Ciocalteu colorimetric assay, commonly used for the evaluation of phenolic compounds in hydro‐alcoholic extracts of EVOO, can also be efficiently applied to verify the compliance to the health claim introduced by EU Reg. 432/2012.